Insect pheromone biochemistry and molecular biology - Blomquist, Gary J.; Vogt, Richard (Richard G.) (Academic Press, 2021)
Insect Pheromone Biochemistry and Molecular Biology, Second Edition, provides an updated and comprehensive review of the biochemistry and molecular biology of insect pheromone biosynthesis and reception. The book ties together historical information with recent discoveries, provides the reader with the current state of the field, and suggests where future research is headed. Written by international experts, many of whom pioneered studies on insect pheromone production and reception, this release updates the 2003 first edition with an emphasis on recent advances in the field. This book will be an important resource for entomologists and molecular biologists studying all areas of insect communication. --